Bullying Sebagai Penghambat Kedewasaan Kristiani Remaja Dalam Perspektif Ensiklik Paus Fransiskus "Christus Vivit” - Rifka Berlian Eka Febriani; Anselmus Joko Prayitno; Yustinus Joko Wahyu Yuniarto; Gregorius Daru Wijoyoko (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
This study examines the theme of non-violence in interactions between adolescents. This study raises the perspective of Pope Francis' encyclical “Christus Vivit” as a Christian perspective in dealing with youth development issues. There are three research focuses, namely describing bullying among adolescents, the role of teachers in schools as controls to prevent bullying, and the role of the Church in Christian assistance in the problem of bullying in adolescents. Researchers use qualitative research methods. To obtain data, researchers used direct interview techniques and zoom meeting-based interviews. Data processing and analysis were carried out in a descriptive way. The research findings show that the psychological impact felt by victims due to bullying is feeling awkward when put together in group work and feeling lonely, afraid to come to school and also afraid to look at social media again. The psychological impact can be felt if you take things too seriously or take your feelings too seriously so that the victim will feel sad. But there are also victims who feel normal because they accept and resolve it in a family and peaceful manner. Students need to be reminded again of the rules that apply in schools, the goal is that all student behavior creates comfort and safety among students. It is better for teachers not only to teach about learning material but to provide character lessons for students on the sidelines of teaching material. The role of the Church should be more aggressive in inviting youth to be involved in church services to develop maturity in their faith so that there is determination not to commit acts of bullying.